The Role of Picture Media in Text – Based Indonesian Language Learning in Elementary Schools - Nafisatul Lubbiya; Vevy Liansari (Green Publisher Indonesia, 2026)
Indonesian is an important subject in Elementary School because it supports the development of students' literacy skills, especially in reading and writing texts. However, in practice, many students have difficulty in understanding and composing texts due to monotonous learning methods and minimal use of concrete media. This study aims to describe the process of using image media in text-based Indonesian language learning and analyze its impact on the ability to understand and compose texts in grade III students of SDI Nurul Yaqin. The method used is qualitative descriptive research with data collection techniques through observation, interviews, documentation, and analysis of student assignment results. The results of the study show that the use of image media, such as story illustrations, mind maps, comics, real photos, and infographics, can improve students' understanding of the contents of the text, strengthen the narrative and descriptive structures, and encourage creativity and learning motivation. The application of image media also helps simplify abstract concepts and create a more interactive learning atmosphere. Thus, image media has proven effective in improving elementary school students' literacy skills, especially in text-based Indonesian language learning. The findings contribute to literacy education theory by demonstrating the mediating role of visual representation in developing metalinguistic awareness and textual competence among young learners. Practical implications include evidence-based guidance for teachers on selecting, sequencing, and integrating picture media strategically within text-based instruction to maximize comprehension gains and compositional fluency.